Skills in the XXI Century Guidance: An Approach to the Costa Rican Reality - Alejandra Gamboa-Jiménez; Juan Ortega-Rojas; Virginia Cerdas-Montano; Manuel Arturo Fallas-Vargas; Juan Vargas-Fonseca (Universidad Nacional, Costa Rica, 2010)
During a long time, the term competence has been used in different fields. Among those fields, and one of the most important, we can mention the educational system, from preschool to university levels. The term has to be understood as one person integral behavior, making him/her able to enter the labor force in the most competitive way. Within the university realm, experts have tried to include the model of competences as a transversal axle into the teaching-learning process. In European universities, such model has been implemented in most of them. In Latin America universities, on the other hand, it has been used in a good number of countries. The importance of early detection of competences among target populations in education has been widely discussed. However, it has been highlighted the necessity of considering romantic or subjective competences, which seem to lack of value in this complex and competitive actual world. The term competence has been classified as genetic competence, or common and specific competence. The latter is related to the knowledge scope. Within the counseling field, specifically, the general and specific competences are deemed highly appropriate for good a work performance. This article focuses on the main antecedents of competences and analyzes this approach from counseling field perspective. In regards to this specific aspect, a survey with professionals in counseling was carried out. Such a survey ends up dealing with some of the competences considered unavoidable for an accurate performance of professionals in counseling. It is important to mention that the competences of the survey mainly point out to genetic competences rather than to specific competences.